BS EN IEC 62841-2-20 AMD1. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 2-20. Particular requirements for hand-held band saws (18th February 2022) - British Standards Institution,
No abstract available